Applying the PROSPER prevention delivery system with middle schools: Emerging adulthood effects on substance misuse and conduct problem behaviors through 14 years past baseline. Issue 4 (15th March 2022) - Spoth, Richard; Redmond, Cleve; Shin, Chungyeol; Trudeau, Linda; Greenberg, Mark T.; Feinberg, Mark E.; Welsh, Janet
Abstract: This study evaluated emerging adult effects of the PROmoting School‐Community‐University Partnerships to Enhance Resilience (PROSPER) universal prevention delivery system implemented in middle schools. Twenty‐eight rural school districts were randomized to intervention and control conditions, with 1985 nineteen‐year‐old participants (90.6% White, 54.1% female) evaluated through age 25. Intent‐to‐treat, multi‐level, point‐in‐time analyses of covariance and growth analyses were conducted. Outcomes were assessed with self‐report measures of substance misuse (lifetime, current, frequency) and conduct problem behaviors. Analyses showed very limited point‐in‐time effects; there were growth pattern effects on measures of illicit drugs, non‐prescribed drugs, cigarettes, and drug problems. When risk moderation was observed, it favored higher‐risk participants. These emerging adult effects concerning slower growth of lifetime misuse combine with more robust adolescent stage findings to support PROSPER's public health value.